The effect of low levels of lead (Pb) in the blood on levels of sphingosine-1-phosphate (S1P) and expression of S1P receptor 1 in the brain of the rat in the perinatal period. (January 2017) - Łukomska, A.; Baranowska-Bosiacka, I.; Budkowska, M.; Pilutin, A.; Tarnowski, M.; Dec, K.; Dołęgowska, B.; Metryka, E.; Chlubek, D.; Gutowska, I.
Abstract: Sphingolipids are the main components of the lipid membrane. They also perform structural functions and participate in many signal transmission processes. One of the bioactive sphingolipids is sphingosine-1-phosphate (S1P), a ligand for five G protein-coupled receptors (S1PRs1-5), which can also act as an intracellular second messenger. S1P is responsible for the stimulation of progenitor cells in the brain, but it can also induce apoptosis of mature neurons. This study is aimed at assessing the effect of pre- and neonatal exposure to permissible Pb concentrations on S1P levels and S1PR1 (EDG1) expression in the prefrontal cortex, cerebellum, and hippocampus of rats. The concentrations of S1P were determined by RP-HPLC, S1PR1 expression was determined by RT PCR and Western Blot, and receptor immunolocalization was determined by immunohistochemistry method. Our results showed that even low blood Pb concentrations, i.e. within the acceptable limit of 10 μg/dL caused changes in the concentration of S1P in the cerebellum, prefrontal cortex, and hippocampus. Our data also showed a significant decrease in the level of S1PR1 in all studied part of brain, without significant changes in S1PR1 gene expression. Pre- and neonatal exposure to Pb also resulted in a decrease in the expression of S1PR1 in glial cells in all regions of the Cornu Ammonis (CA1-CA4) and Dentate Gyrus in the hippocampus, as well as in all layers of the cerebellum and prefrontal cortex, compared to the unexposed control group. Highlights: The blood Pb in the exposed group is higher than the control group and it is correlated with brain Pb concentration. Exposure to Pb is responsible for changes in the concentration of S1P in the cerebellum, prefrontal cortex and hippocampus. Lead exposure cause decrease expression of S1PR1 in the glial cells in the hippocampus, cerebellum and prefrontal cortex.